Estudos ecológicos de comunidades microbianas tratando glicerol em condições anaeróbias pela aplicação de biologia molecular - Vasconcelos, Eduardo Augusto Felipe de (2017)
Molecular biology techniques applied in anaerobic digestion allow the study of microbial ecology and community structure in bioreactors. Glycerol is a byproduct of transesterification and can be used to produce hydrogen by anaerobic digestion, so understanding the microbial interactions is necessary to assess the relation among biological, operational and functional factors, improving the processes and the performance of the system. This research aimed to study the variations of diversity, richness and functional organization of the microbial community, analyzing ecological and operational parameters, as well as the functionality and productivity of anaerobic reactors. Hydrogenic UASB reactors were operated and monitored under OLR increases. The feeding used were: crude glycerol and pure glycerol (two phases), with nutrient solution in all the affluents. The parameters analyzed were: COD, metabolites, pH, flow, volume and gas composition, functional organization, range-weighted richness, Shannon diversity, and species found by Sanger sequencing. Sludge samples were collected and stored at each OLR change and the DNA was extracted and amplified with primers containing GC clamps for Bacteria and Archaea domains, followed by DGGE on polyacrylamide gel (8%) for both domains. The resulting bands were excised, amplified, purified and sequenced. The results showed that in OLR below 30 kg COD/m 3.d-1there was an increase in the carrying capacity and stability of the environment, with low functional organization and increased richness and diversity in both studies, for both domains and substrates. Population parameters of Bacteria in the following stages decreased and functional organization increased, indicating a gradual increase in the level of community specialization. Populational increases were greater with residual glycerol than with pure due to the specificity of the second substrate compared to the residual, a more generalist substrate. The ecological parameters of Archaea in the later stages decreased due to inhibition by substrate excess, which promoted an increase in the productivity of the bacterial domain. Pure glycerol proved to be a worse substrate for the development of methanogens than the residual.